Ascending Aortic Aneurysm, Wandering towards Old Problem with New Insight - Tiwari, KK; Bevilacqua, S; Salvati, A; Varone, E; Solinas, M; Glauber, M (Journal of Universal College of Medical Sciences, 2014)
Ascending aortic aneurysm is a silent and highly lethal disease. Generally, ascending aorta grows asymptomatically until it dissect or rupture. In case of acute complication mortality is as high as 90%, whereas if treated on time mortality and morbidity decreases significantly. Pathophysiology of the Ascending aortic aneurysm is a complex process. Aorta itself is an organ and it should not be considered merely as a tube transporting blood from heart to the organs. Several non-invasive and invasive imaging methods are available at disposition to diagnose this indolent killer at early stage. However, discrepancies exists about when to operate these patients. Several other methods has been reported to identify these patients at risk of dissection or rupture. Conservative treatment could be used in patients with small aortic diameter, but effectiveness of such approach is under scrutiny. Emerging endovascular treatment using stents should be advocated with caution. Surgical treatment, the gold standard, is recommended for asymptomatic patients with aortic diameter of 5.5cm, whereas 4-4.5cm for patients with Marfan's disease. Postoperative morbidity and mortality has significantly decreased due to better anesthetic management, improved surgical techniques and progress in preoperative and postoperative care. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11175 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 49-59